Proceedings of the 2021 Conference of the North American Chapter of the Association for Computational Linguistics: Human Langua 2021
DOI: 10.18653/v1/2021.naacl-main.294
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Bias in the Multimodal Analysis of Financial Earnings Calls

Abstract: Volatility prediction is complex due to the stock market's stochastic nature. Existing research focuses on the textual elements of financial disclosures like earnings calls transcripts to forecast stock volatility and risk, but ignores the rich acoustic features in the company executives' speech. Recently, new multimodal approaches that leverage the verbal and vocal cues of speakers in financial disclosures significantly outperform previous stateof-the-art approaches demonstrating the benefits of multimodality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In a similar manner, a multi-modal prediction model also worked well in predicting stock price volatility Sawhney et al [50], as well as the neural attentive alignment model capturing interdependencies between verbal and vocal modalities [49,51]. The most recent work found that there is gender bias in multi-modal financial forecasts [52] and that managers modify the way they talk knowing that machines are listening [10].…”
Section: Vocal Features In Financementioning
confidence: 88%
“…In a similar manner, a multi-modal prediction model also worked well in predicting stock price volatility Sawhney et al [50], as well as the neural attentive alignment model capturing interdependencies between verbal and vocal modalities [49,51]. The most recent work found that there is gender bias in multi-modal financial forecasts [52] and that managers modify the way they talk knowing that machines are listening [10].…”
Section: Vocal Features In Financementioning
confidence: 88%
“…Moreover, multimodal machine learning was used by [2] and [43] for credit rating prediction and measurement of persuasiveness respectively. [1] investigated biases in the multimodal analysis of financial earnings calls. Finally, [44] provide critical analysis of how corporate disclosure has been reshaped over last couple of years due to increasing use of NLP in Finance.…”
Section: Related Workmentioning
confidence: 99%
“…Quarterly analyst reports (in English) on a large number of public firms in the U.S. constitute the raw dataset for our model. These analysts reports were collected from Zacks Equity Research and were available to us from Nexis Uni license 1 . Before the data is passed on to labelling functions 1.…”
Section: Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge the presence of gender bias in our study, given the imbalance in the gender ratio of speakers of the calls. We also acknowledge the demographic bias (Sawhney et al, 2021a) in our study as the companies are organizations within the public stock market of United States of America and may not generalize directly to non-native speakers.…”
Section: Ethical Considerations and Limitationsmentioning
confidence: 99%